Ultrasound-guided quadratus lumborum block as a postoperative analgesic technique for laparotomy - Vasanth Rao Kadam (Wolters Kluwer Medknow Publications, 2013)
The quadratus lumborum (QL) block as a postoperative analgesic method following abdominal surgery has been described by Blanco for superficial surgeries but not used for major laparotomy. This ipsilateral QL block had low pain scores and opioid use on day one with sensory block upto T8-L1. The options of various volume used and pros and cons are discussed.